2021
DOI: 10.1146/annurev-animal-090120-115444
|View full text |Cite
|
Sign up to set email alerts
|

Coral Probiotics: Premise, Promise, Prospects

Abstract: The use of Beneficial Microorganisms for Corals (BMCs) has been proposed recently as a tool for the improvement of coral health, with knowledge in this research topic advancing rapidly. BMCs are defined as consortia of microorganisms that contribute to coral health through mechanisms that include ( a) promoting coral nutrition and growth, ( b) mitigating stress and impacts of toxic compounds, ( c) deterring pathogens, and ( d) benefiting early life-stage development. Here, we review the current proposed BMC ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
146
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 142 publications
(149 citation statements)
references
References 159 publications
2
146
0
1
Order By: Relevance
“…On the one hand, such observations support the notion that microbiome community changes can support host ecological adaption to environmental change (Reshef et al, 2006;Voolstra and Ziegler, 2020). On the other hand, the premise of flexibility gives rise to the idea of probiotics, i.e., inoculation with beneficial bacteria to support metaorganism stress resilience (Peixoto et al, 2017(Peixoto et al, , 2019(Peixoto et al, , 2021. The latter is gaining attention with regards to reef-building corals given the alarming loss of coral reef cover over recent decades (Hughes et al, 2017a(Hughes et al, , 2020.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…On the one hand, such observations support the notion that microbiome community changes can support host ecological adaption to environmental change (Reshef et al, 2006;Voolstra and Ziegler, 2020). On the other hand, the premise of flexibility gives rise to the idea of probiotics, i.e., inoculation with beneficial bacteria to support metaorganism stress resilience (Peixoto et al, 2017(Peixoto et al, , 2019(Peixoto et al, , 2021. The latter is gaining attention with regards to reef-building corals given the alarming loss of coral reef cover over recent decades (Hughes et al, 2017a(Hughes et al, , 2020.…”
Section: Discussionmentioning
confidence: 65%
“…It has been shown that the SML of corals is highly dynamic, with SML being cyclically shed (Bythell and Wild, 2011). This is thought to prevent pathogen colonization from the surrounding environment (Shnit-Orland and Kushmaro, 2009;Glasl et al, 2016), but might also explain the flexible microbial association of corals commonly found across different environments (Roder et al, 2015;Röthig et al, 2016bRöthig et al, , 2017Ziegler et al, 2017;Voolstra and Ziegler, 2020) and may contribute to the efficacy of coral probiotics (Peixoto et al, 2017(Peixoto et al, , 2021. At a more basal level, the difference in surface topography between hydrozoans and anthozoans argues for the need of having distinct cnidarian models to reflect the implied microbial association differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to describe, understand, and culture specific symbionts from any given organism (like corals) also opens up the potential to utilize them as probiotics to restore degraded habitats ( 53 , 61 ). For example, specific traits found in certain coral-associated bacteria, such as the presence of the genes nifH (nitrogenase), nirK (nitrite reductase), or dmdA (DMSP demethylase) involved in nitrogen and sulfur cycling, or those known to control pathogens, the enzymatic mitigation of reactive oxygen species (ROS) or other toxic compounds, may have roles in increasing coral health when the host is experiencing stress ( 53 , 63 , 81 , 82 ). Identifying these traits via molecular analyses and laboratory tests using cultured bacteria with defined coral hosts will allow for the more rapid administration of native bacteria with the potential to help rehabilitate damaged corals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rosado et al ( 53 ) showed that application of so-called “beneficial microorganisms for corals” (or BMCs) increases the resilience of the coral to temperature stress and pathogen challenge. However, despite the demonstrated importance of BMCs ( 63 ), a centralized and curated collection of isolates obtained from corals and their associated genetic information does not currently exist. Moreover, many culture-based studies often focus on relatively few bacteria (targeted for pathogenic agents for example), meaning a large-scale comparison of which bacterial isolates can be cultured and their genetic information is currently missing.…”
Section: Introductionmentioning
confidence: 99%